2012
DOI: 10.1016/j.jneumeth.2012.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Distal hypoxic stroke: A new mouse model of stroke with high throughput, low variability and a quantifiable functional deficit

Abstract: C57BL/6J are the most commonly used strain of mouse for stroke experiments but vascular anatomy of the Circle of Willis within this strain is extremely variable and the cortex has extensive collateralization. This causes large variability in stroke models that target the middle cerebral artery proximally and confers resistance to ischemia in those that target it distally. We tested the hypothesis that by combining distal middle cerebral artery occlusion with 1 hour of hypoxia, we could generate a large lesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 22 publications
2
67
0
Order By: Relevance
“…26 For this set of studies, ventral photographs of carbon-black-perfused brains revealed that the posterior communicating artery was present either unilaterally or bilaterally in all mice except one.…”
Section: Arteriolar Flowmentioning
confidence: 90%
“…26 For this set of studies, ventral photographs of carbon-black-perfused brains revealed that the posterior communicating artery was present either unilaterally or bilaterally in all mice except one.…”
Section: Arteriolar Flowmentioning
confidence: 90%
“…Distal middle cerebral artery occlusion (DMCAO) plus hypoxia (DH stroke) was performed on C57BL/6 mice, as previously described (Doyle et al, 2012; Nguyen et al, 2016). Mice were anesthetized by isoflurane inhalation, and an incision was made to expose the temporalis muscle.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were randomly allocated into stroke and sham experimental groups. This stroke model creates a large infarct comprising approximately 25% of the stroked hemisphere, has little variability, and excellent long-term survivability (Doyle et al, 2012). Hypoxia is necessary with this model because C57BL/6 mice that undergo DMCAO without hypoxia have significantly smaller infarcts (Doyle et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations